Towards a Better Understanding of Ubiquitous Cloud Computing - Vahdat-Nejad, Hamed; Eilaki, Shaghayegh Ostadi; Izadpanah, Shaghayegh (International journal of cloud applications and computing, 2018)
Ubiquitous Cloud Computing has been recently proposed as a new hybrid computing model. This paradigm has two aspects: (a) Making use of cloud services to realize context-awareness (especially for mobile phones) and (b) Introducing a new and hybrid computing model. Likewise, this paper mainly involves two subjects: To deeply investigate previous cloud services that have been utilized to design context-aware systems, and to propose an open architecture for the “Ubiquitous Cloud Computing” paradigm. The aim of this article is to technically discuss mutual trends of ubiquitous and cloud computing, to foster the dissemination of state-of-the-art research in this area, and to present future research directions.